Evaluation of Integration and Human Resources in Information Technology Governance using COBIT 2019: PT. Pelabuhan Indonesia Tanjung Priok Branch - Timotius Ammar Karo Karo; Ahmad Faza (Universitas Bina Darma, 2023)
The Tanjung Priok Branch of PT. Pelabuhan Indonesia is a state-owned enterprise fully owned by the Ministry of State-Owned Enterprises, representing the Republic of Indonesia. Despite its commitment to governance, the branch encounters certain deficiencies. These include challenges related to system optimization, hindering the realization of effective processes. Moreover, there's a recognized need to enhance the expertise of the workforce to better leverage existing knowledge assets. To address these concerns, a comprehensive study focused on the IT governance of the Tanjung Priok Branch was conducted. The research employed the COBIT 2019 framework to evaluate the IT governance landscape. The investigation pinpointed areas requiring attention and enhancement within the organization. Notably, three key domains emerged as pertinent: APO08 - Managed Relationship, APO11 - Managed Quality, and BAI08 - Managed Knowledge. The assessment revealed noteworthy insights into the organization's IT governance structure. The evaluation of the APO08 process indicated that its performance fell short of the anticipated target, remaining at level 3. On the other hand, the APO11 process achieved the desired level, reaching level 4 and demonstrating significant progress. Similarly, the BAI08 process attained level 4, successfully meeting the intended target. These findings shed light on areas of accomplishment as well as those requiring further attention. To propel the Tanjung Priok Branch of PT. Pelabuhan Indonesia towards its envisioned level of excellence, it's imperative to address the identified gaps and build upon the areas of success. This strategic approach will pave the way for the realization of optimized IT governance, efficient processes, and empowered human resources, aligning with the organization's overarching objectives.